Józef Tischner’s early thought as phenomenological axiology - Karpinski, Andrew (Studies in East European thought, 2025)
Józef Tischner, a Polish twentieth century priest and philosopher, is mostly known for his ideas relating to the theme of solidarity, as well as for his original ‘philosophy of drama’. This article examines selected aspects of his early philosophy, without which those two major contributions cannot be properly understood. I begin by a brief synopsis of three thinkers which have exerted major influence on Tischner – Edmund Husserl, Max Scheler, and Roman Ingarden. I then proceed to recount Tischner’s own early philosophy as an investigation of human self-awareness, showing how several ideas (such as ‘solidarization’) contribute to Tischner’s later thought. Finally, I offer a brief critical remark to Tischner’s work – namely, whether it is possible to argue for an ultimately axiological constitution of self-awareness, without taking a stance on the question related to the nature and existence of values.